2015
DOI: 10.1039/c5tc00065c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of poly-Schiff bases with a donor–acceptor structure containing thiophene units as thermoelectric materials

Abstract: A Poly-Schiff base (PSB) with a donor–acceptor structure was successfully synthesized and was blended with different fillers to prepare polymer–inorganic thermoelectric (TE) composites. It is the first time that PSB was treated as a TE material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…The further addition of Bi 2 Te 3 in G/50 wt.% PTh composites from 5% to 10% slightly decreased the value of the Seebeck coefficient from 23.3 lV/K to 20.4 lV/K, which could be attributed to the lower number of interfaces formed between the fillers and matrix because of the higher density of Bi 2 Te 3 than that of G and PTh. 18 Similar results were also observed for composites C and D with PTh content of about 20 wt.%; they also exhibited much higher Seebeck coefficient values of 15.9 lV/K and 14.2 lV/K than that of G/20 wt.% PTh composite 9.36 lV/K at 30°C. 15 These results also demonstrate that the addition of a small amount of Bi 2 Te 3 into Bi 2 Te 3 /G/PTh composites indeed increased the Seebeck coefficient of these composites.…”
Section: Thermoelectric Properties Of Bi 2 Te 3 /G/pth Compositessupporting
confidence: 87%
See 1 more Smart Citation
“…The further addition of Bi 2 Te 3 in G/50 wt.% PTh composites from 5% to 10% slightly decreased the value of the Seebeck coefficient from 23.3 lV/K to 20.4 lV/K, which could be attributed to the lower number of interfaces formed between the fillers and matrix because of the higher density of Bi 2 Te 3 than that of G and PTh. 18 Similar results were also observed for composites C and D with PTh content of about 20 wt.%; they also exhibited much higher Seebeck coefficient values of 15.9 lV/K and 14.2 lV/K than that of G/20 wt.% PTh composite 9.36 lV/K at 30°C. 15 These results also demonstrate that the addition of a small amount of Bi 2 Te 3 into Bi 2 Te 3 /G/PTh composites indeed increased the Seebeck coefficient of these composites.…”
Section: Thermoelectric Properties Of Bi 2 Te 3 /G/pth Compositessupporting
confidence: 87%
“…We attempted to prepare the samples for measurements by using our previous reported method. 18 In order to confirm that the pressure we used to prepare samples has no big influence on the thermoelectric performance, we used small pressure differences (15 MPa and 20 MPa) for preparing samples of 5% Bi 2 Te 3 /40%G/PTh, and found that small pressure differences has limited effects on thermoelectric parameters of our composites (such as power factor and thermal conductivity), as shown in Table SI (Supporting Information). The cuboid specimen with dimensions of 16.0 mm 9 5.10 mm 9 3.0 mm was prepared under a pressure of 15 MPa for the electrical properties measurement, and the disk specimen with a diameter of 15.0 mm and a height of 3.0-4.0 mm was prepared under a pressure of 20 Mpa for the thermal conductivity measurement.…”
Section: Methodsmentioning
confidence: 91%
“…The molecular structures of conjugated polymers play a critical role in determining their thermoelectric performance. Conjugated polymers are well known to exhibit strong stacking interactions, and these strong interactions can facilitate charge‐carrier transport and enhance the electrical conductivity of bulk conjugated polymers . On the basis of the equation for ZT , good thermoelectric materials must combine both high electrical conductivities and high Seebeck coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…The cuboid specimen with dimensions of 16.0 mm × 5.10 mm × 3.0 mm was prepared under a pressure of 15 MPa for the electrical properties measurement, and the disk specimen with a diameter of 15.0 mm and a height of 3.0–4.0 mm was prepared under a pressure of 20 MPa for the thermal conductivity measurement. According to our previous report , two different pressures were applied for the electrical properties and thermal conductivity measurements to obtain more successful samples because of different sample shapes. It was found that the Seebeck coefficient, thermal conductivity, and sample density are only slightly affected under the two tested pressures.…”
Section: Methodsmentioning
confidence: 99%